2018
DOI: 10.1161/circep.118.006497
|View full text |Cite
|
Sign up to set email alerts
|

QRS Area Is a Strong Determinant of Outcome in Cardiac Resynchronization Therapy

Abstract: Background: The combination of left bundle branch block (LBBB) morphology and QRS duration is currently used to select patients for cardiac resynchronization therapy (CRT). These parameters, however, have limitations. This study evaluates the value of QRS area compared with that of QRS duration and morphology in the association with clinical and echocardiographic outcomes in a large cohort of CRT patients. Methods: A retrospective multicentre study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 27 publications
8
94
0
Order By: Relevance
“…Patients with LOR <12 had significantly lower mean QRS area than patients with LOR ≥12. QRS area is a measure of nonopposed electrical forces, and high values suggest more significant dyssynchrony and have also been associated with greater response to CRT 6,7 . When QRS area was included in multivariable models along with QRS duration, LOR <12 remained strongly predictive of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with LOR <12 had significantly lower mean QRS area than patients with LOR ≥12. QRS area is a measure of nonopposed electrical forces, and high values suggest more significant dyssynchrony and have also been associated with greater response to CRT 6,7 . When QRS area was included in multivariable models along with QRS duration, LOR <12 remained strongly predictive of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac resynchronization therapy (CRT) improves cardiac function, facilitates LV reverse remodeling, and reduces mortality in patients with LBBB 3 . Electrocardiogram (ECG) features such as QRS duration, area, and morphology have been previously shown to be important predictors of response to CRT 4‐7 . Prior work has demonstrated that LBBB patients with a low ECG lead one ratio (LOR) of positive/negative amplitudes have lower LV ejection fraction (LVEF) and worse clinical outcomes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies have reported a strong positive correlation between QRS area and CRT response and that this correlation is as valuable as the other current ECG criteria. QRS area may be predictive of CRT response in patients with non-wide left bundle branch block [12]. In addition to ECG, magnetic resonance and other tests were used in recent studies to determine left ventricular dyssynchrony.…”
Section: Preparation For Implantationpatient Selectionmentioning
confidence: 99%
“…There has been a great deal of interest in attempting to predict the exact site of LBBB as this could have important implications not only for the siting of the coronary sinus LV lead but also predicting positive LV remodeling. A number of ECG markers of remodeling have been proposed including QRS duration, QRS area and the morphology of the intrinsicoid deflection (9)(10)(11)(12). Fundamentally, if there is an excess of fibrosed myocardium, it is unlikely there is sufficient myocardial reserve to achieve adequate remodeling even if the lead is targeted outside scar.…”
Section: Defining Left Bundle Branch Block-is This the Roadblock To Cmentioning
confidence: 99%
“…However, only a small proportion of patients have such broad QRS durations which has spurred investigation of other ECG markers to predict response even in non-LBBB cases. A recent study evaluated the QRS area which is an indicator of focal fibrosis in 1492 CRT recipients (9,11). QRS area identified patients who did not experience the primary end point (death, transplantation, left ventricular assist device implantation) & echocardiographic remodeling better than QRS morphology and QRS duration.…”
Section: Defining Left Bundle Branch Block-is This the Roadblock To Cmentioning
confidence: 99%